Efectos de la aplicación de diferentes abonos orgánicos en el cultivo de pimiento Capsicum annuum L. - Chimborazo Chimborazo, Jorge Marcial (2022)
The pepper is a vegetable that represents an important agricultural activity, for this reason new alternatives are sought so that the production is profitable and healthy. Three organic fertilizers (compost, bocashi and earthworm humus) and fertilizer (NPK 10-30-10) were used, the complete randomized block design was used with four treatments and four repetitions, the California pepper hybrid (Capsicum annuum L). The objectives were to determine the effects of organic fertilizers on the physiological development of the crop.